The Causal Effects Between Circulating Inflammatory Proteins and Osteoarthritis: A Mendelian Randomization and Transcriptomic Analysis - Lin S; Wu C; Pan Y (Journal of Pain Research, 2025)
Shaoru Lin,1 Changwu Wu,2,3 Yimin Pan2 1Department of Orthopedics, The Second Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of China; 2Department of Neurosurgery, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 3National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Yimin Pan, Department of Neurosurgery, Xiangya Hospital, Central South University, No. 87 Xiangya Road, Changsha, 410008, People’s Republic of China, Email yimin.pan@foxmail.comBackground: Observational studies have demonstrated the correlation between various inflammatory proteins and osteoarthritis (OA). However, the causal relationship and directionality between them are still unclear. This study aims to analyze the potential causal relationship between circulating inflammatory proteins and OA using Mendelian randomization (MR) analysis.Methods: This study used bidirectional two-sample MR analysis, employing the inverse variance-weighted as the primary MR method. The GWAS summary data for OA were derived from The Musculoskeletal Knowledge Portal, while the GWAS summary data for 91 circulating inflammatory proteins were obtained from a recently published study. Furthermore, this study used two transcriptomic cohorts from the GEO database to explore differentially expressed inflammation-related genes (IRGs) in OA and identify key inflammatory markers.Results: This study provides suggestive evidence. The forward two-sample MR analysis found that the levels of urokinase-type plasminogen activator, adenosine deaminase, C-C motif chemokine 19, interleukin-10 receptor subunit alpha and latency-associated peptide transforming growth factor beta 1 have causal effects on lower risk of OA, and the levels of fractalkine, C-X-C motif chemokine 1, hepatocyte growth factor and interleukin-8 have causal effects on higher risk of OA. Reverse two-sample MR analysis showed that hip OA has causal effects on the increased levels of caspase 8, protein S100A12, interleukin-10 receptor subunit alpha, interleukin-7 and monocyte chemoattractant protein 2 and a causal effect on the decreased level of fms-related tyrosine kinase 3 ligand. Knee OA has a causal effect on the increased level of monocyte chemoattractant protein-3 and decreased level of interleukin-1-alpha respectively. Furthermore, we identified six key OA-related IRGs through comprehensive transcriptomic analysis, which could serve as potential diagnostic biomarkers for OA.Conclusion: This study supports the causal relationship between OA and specific circulating inflammatory proteins and develops potential OA-related inflammatory biomarkers.Keywords: osteoarthritis, circulating inflammatory proteins, Mendelian randomization study, causal relationship, inflammation-related genes, biomarker